1998
DOI: 10.1002/hep.510270203
|View full text |Cite
|
Sign up to set email alerts
|

Selective impairment of endothelium-mediated vasodilation in liver transplant recipients with cyclosporin A -induced hypertension

Abstract: Arterial hypertension is commonly observed in orthotopic liver transplantation (OLT) recipients receiving cyclosporin A (CsA), but the precise pathogenetic mechanisms remain partially unknown. The aim of this study was to investigate endothelium-dependent and -independent dilation and adrenergic constriction of resistance vessels of OLT recipients treated with CsA. Vascular reactivity was examined in 22 OLT patients, 10 with and 12 without arterial hypertension, and in 10 control subjects by assessing the fore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
5
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 27 publications
(39 reference statements)
2
5
0
Order By: Relevance
“…Both ET‐1 and NO levels were normal in these patients. This is in line with previous data (16, 37). Together with the fact that other vasodilatory mediators such as adrenomodulin and atrial natriuretic peptide were increased after OLT (38), this suggests that the vasodilatory capacities of OLT patients are normal.…”
supporting
confidence: 94%
See 1 more Smart Citation
“…Both ET‐1 and NO levels were normal in these patients. This is in line with previous data (16, 37). Together with the fact that other vasodilatory mediators such as adrenomodulin and atrial natriuretic peptide were increased after OLT (38), this suggests that the vasodilatory capacities of OLT patients are normal.…”
supporting
confidence: 94%
“…After organ transplantation, an impaired balance between vasodilatory and vasoconstrictive mediators has been reported, with decreased endothelial NO bioavailability, enhanced sensitivity to ET-1 and significantly impaired FMD (8)(9)(10)(11)(12)(13)(14)(15). Few data are available concerning endothelial function after OLT (16,17), but cardiovascular complications are more prevalent in liver transplant recipients than in the general population (18). Among other etiologies, the use of calcineurin inhibitors (CNI) such as tacrolimus (TAC) has been cited as a cause of altered endothelial function (19,20).…”
Section: Oliviermentioning
confidence: 99%
“…Nevertheless, the doses of CsA we used were not particularly high and were reduced after the 4th month of transplantation (C0 M7: 139 ± 10 ng/ml) [34,35]. Therefore, because CsA is not always associated with endothelial dysfunction [5,51,52] and conversion to CNI‐free regimen may be insufficient to restore endothelial function [6,45], additional mechanisms may be involved. This includes a direct beneficial effect of SRL on vascular endothelium [17,28], although controversial [30–32], or a vascular synergistic effect of SRL and MMF preventing endothelin‐1 release and oxidative stress [53,54].…”
Section: Discussionmentioning
confidence: 99%
“…The association of Hcy with hypertension is more intriguing. Renal artery vasoconstriction has been proposed as the main cause of posttransplantation hypertension,35 and recent studies have demonstrated a defect in post‐OLT endothelial‐mediated vasodilation,36 that could also be produced by Hcy 15. Drugs may be involved as well.…”
Section: Discussionmentioning
confidence: 99%